Purpureocillium lilacinum and Metarhizium marquandii as plant growth-promoting fungi - Baron, Noemi Carla [UNESP]; de Souza Pollo, Andressa [UNESP]; Rigobelo, Everlon Cid [UNESP] (PeerJ, 2020)
Background: Especially on commodities crops like soybean, maize, cotton, coffee and others, high yields are reached mainly by the intensive use of pesticides and fertilizers. The biological management of crops is a relatively recent concept, and its application has increased expectations about a more sustainable agriculture. The use of fungi as plant bioinoculants has proven to be a useful alternative in this process, and research is deepening on genera and species with some already known potential. In this context, the present study focused on the analysis of the plant growth promotion potential of Purpureocillium lilacinum, Purpureocillium lavendulum and Metarhizium marquandii aiming its use as bioinoculants in maize, bean and soybean. Methods: Purpureocillium spp. and M. marquandii strains were isolated from soil samples. They were screened for their ability to solubilize phosphorus (P) and produce indoleacetic acid (IAA) and the most promising strains were tested at greenhouse in maize, bean and soybean plants. Growth promotion parameters including plant height, dry mass and contents of P and nitrogen (N) in the plants and in the rhizospheric soil were assessed. Results: Thirty strains were recovered and characterized as Purpureocillium lilacinum (25), Purpureocillium lavendulum (4) and Metarhizium marquandii (1). From the trial for P solubilization and IAA production, seven strains were selected and inoculated in maize, bean and soybean plants. These strains were able to modify in a different way the evaluated parameters involving plant growth in each crop, and some strains distinctly increased the availability of P and N, for the last, an uncommon occurrence involving these fungi. Moreover, the expected changes identified at the in vitro analysis were not necessarily found in planta. In addition, this study is the first to evaluate the effect of the isolated inoculation of these fungi on the growth promotion of maize, bean and soybean plants.
Keywords: Maize; Metarhizium marquandii; Plant-growth-promoting; Purpureocillium lilacinum; Soybean